THE ROLE OF IMMUNOINFLAMMATORY MARKERS IN THE PROGNOSIS AND RESECTABILITY OF PANCREATIC ADENOCARCINOMA - EYFF,Tatiana Falcão (2018)
ABSTRACT Background: Pancreatic adenocarcinoma has a high mortality rate. A prognostic tool is essential for a better risk stratification. The neutrophil/lymphocyte ratio and adaptations and the platelet/lymphocyte ratio seem promising for this purpose. Aim: Evaluate the prognostic value of neutrophil/lymphocyte ratio, derived neutrophil/lymphocyte ratio and platelet/lymphocyte ratio, analyze the ideal cutoff values and investigate their utility in predicting resectability. Methods: Data were collected of patients with pancreatic adenocarcinoma in Hospital de Clínicas de Porto Alegre between 2003 and 2013. The studied ratios were determined by blood count collected at hospital admission and after two cycles of palliative chemotherapy. Results: Basal neutrophil/lymphocyte ratio, derived neutrophil/lymphocyte ratio and platelet/lymphocyte ratio did not have prognostic impact in survival (p=0.394, p=0.152, p=0.177 respectively). In subgroup analysis of patients submitted to palliative chemotherapy, neutrophil/lymphocyte ratio, derived neutrophil/lymphocyte ratio and platelet/lymphocyte ratio determined after two cycles of chemotherapy were prognostic for overall survival (p=0.003, p=0.009, p=0.001 respectively). The ideal cutoff values found were 4,11 for neutrophil/lymphocyte ratio (sensitivity 83%, specificity 75%), 2,8 for derived neutrophil/lymphocyte ratio (sensitivity 87%, specificity 62,5%) and 362 for platelet/lymphocyte ratio (sensitivity 91%, specificity 62,5%), Neutrophil/lymphocyte ratio, derived neutrophil/lymphocyte ratio and platelet/lymphocyte ratio were not able to predict resectability (p=0.88; p=0.99; p=0.64 respectively). Conclusions: Neutrophil/lymphocyte ratio, derived neutrophil/lymphocyte ratio and platelet/lymphocyte ratio are useful as prognostic markers of overall survival in patients with pancreatic adenocarcinoma submitted to palliative chemotherapy. Its use as resectability predictor could not be demonstrated.